Spatial and temporal variability of seawater pCO2 within the Canadian Arctic Archipelago and Baffin Bay during the summer and autumn 2011. (15th March 2018) - Geilfus, N.-X.; Pind, M.L.; Else, B.G.T.; Galley, R.J.; Miller, L.A.; Thomas, H.; Gosselin, M.; Rysgaard, S.; Wang, F.; Papakyriakou, T.N.
Abstract: The partial pressure of CO2 in surface water ( p CO2 sw ) measured within the Canadian Arctic Archipelago (CAA) and Baffin Bay was highly variable with values ranging from strongly undersaturated (118 µatm) to slightly supersaturated (419 µatm) with respect to the atmospheric levels (~386 μatm) during summer and autumn 2011. During summer, melting sea ice contributed to cold and fresh surface water and enhanced the ice-edge bloom, resulting in strong p CO2 sw undersaturation. Coronation Gulf was the only area with supersaturated p CO2 sw, likely due to warm CO2 -enriched freshwater input from the Coppermine River. During autumn, the entire CAA (including Coronation Gulf) was undersaturated, despite generally increasing p CO2 sw . Coronation Gulf was the one place where p CO2 sw decreased, likely due to seasonal reduction in discharge from the Coppermine River and the decreasing sea surface temperature. The seasonal summer-to-autumn increase in p CO2 sw across the archipelago is attributed in part to the continuous uptake of atmospheric CO2 through both summer and autumn and to the seasonal deepening of the surface mixed layer, bringing CO2 -rich waters to the surface. These observations demonstrate how freshwater from sea ice melt and rivers affect p CO2 sw differently. The general p CO2 sw undersaturation during summer-autumn 2011 throughout the CAA and Baffin Bay give an estimated net oceanic sink for atmospheric CO2 over the study period of 11.4 mmol CO2 m −2 d −1, assuming no sea-air CO2 flux exchange across the sea-ice covered areas. Highlights: The overall p CO2 undersaturation in the CAA allows the area to act as a net sink for atmospheric CO2 from summer to autumn. In summer, the surface water p CO2 is undersaturated due to sea ice melt and associated ice-edge phytoplankton bloom. In autumn, the surface water p CO2 remains undersaturated due to decreasing sea surface temperature and freshwater input.